Institutional aspects of regulation and quality assurance of audit activity in Ukraine as a component of development of financial reporting quality audit - T.M. Kochyn (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The study found that the use of audit tools and appropriate analytical procedures by auditors and audit entities as a whole in the course of providing us with audit services is a fundamental basis for ensuring and developing the organizational and methodological framework for conducting the audit of financial statements. In turn, it is necessary to assess the current state of the quality of audit services provided to auditors and audit entities in Ukraine in order to identify issues and seek directions for improving the organization process, conduct financial statements audit, and improve the effectiveness of the results of these control procedures. The study found that quality control of audit services can take on the internal and external forms of its organization with respect to auditors and audit entities. When considering the issues of auditing regulation, the institutional aspects of quality assurance of the audit activity were illustrated. The article found that, to date, the world-wide recognized models of regulation of audit activity are: the model of state regulation of audit activity; model of self-regulation or public regulation of audit activity; a mixed model of auditing regulation. It should be noted that the quality of financial statements on which financial information users make decisions depends not only on the quality of the disclosure of such information, but also on the quality of the audit report, where the auditor's opinion on whether the financial statements are free from material misstatement and consistent with the chosen conceptual basis. In this regard, particular attention should be paid when auditing procedures to familiarize the client with the environment to understand the risks of lower quality of financial statements. Keywords: ; ; ; ; .